Surface Plasmon Resonance-Based Gold-Coated Hollow-Core Negative Curvature Optical Fiber Sensor - J. Divya; S. Selvendran (Biosensors, 2023)
The hollow-core fiber-based sensor has garnered high interest due to its simple structure and low transmission loss. A new hollow-core negative-curvature fiber (HC-NCF) sensor based on the surface plasmon resonance (SPR) technique is proposed in this work. The cladding region is composed of six circular silica tubes and two elliptical silica tubes to reduce fabrication complexity. Chemically stable gold is used as a plasmonic material on the inner wall of the sensor structure to induce the SPR effect. The proposed sensor detects a minor variation in the refractive indices (RIs) of the analyte placed in the hollow core. Numerical investigations are carried out using the finite element method (FEM). Through the optimization of structural parameters, the maximum wavelength sensitivity of 6000 nm/RIU and the highest resolution of 2.5 × 10−5 RIU are achieved in the RI range of 1.31 to 1.36. In addition, an improved figure of merit (FOM) of 2000 RIU−1 for Y-polarization and 857.1 RIU−1 for X-polarization is obtained. Because of its simple structure, high sensitivity, high FOM, and low transmission loss, the proposed sensor can be used as a temperature sensor, a chemical sensor, and a biosensor.